Teknik two step-cutaneous plasty shaft Penis dengan scrotal skin pada kasus parafinoma penis: laporan kasus - Putu Kurnia Darma Pratama; I Putu Gde Sanjaya (DiscoverSys Inc., 2019)
Background: Penile injection of paraffin is one of procedure that people think can increase penile size. Nevertheless, many people do not know if paraffin injection causes significant adverse effects such as penile paraffinoma. A surgical procedure by wide excision of skin and subcutaneous tissue infiltrated by paraffin continued with appropriate phalloplasty could be done as definitive therapy with the good aesthetic and functional result. This case report aims to present penile parafinoma or sclerosing lipogranuloma due to subcutaneous penile injection of paraffin, its management and the result after surgical procedure.Case: A 40-year-old man came to the Urology Polyclinic, Mangusada Badung Regional Hospital who presented with penile swelling and pain for 3 days. There was a history of subcutaneous penile injection of paraffin about one-year ago by non-medical personnel. On examination of genital organ, there was swelling on entire penile skin with tenderness and induration. A surgical procedure was performed using a two-step cutaneous plasty technique with scrotal flaps on the shaft of the penis. After two months, the surgical procedure gave an excellent penile aesthetic and functional result.Conclusion: Penile parafinoma is a lipogranulomatous inflammatory reaction due to injection of paraffin substance, which cases are still found today, especially in Indonesia. Reconstructive surgery is the definitive therapy to overcome aesthetic or functional problems.